2003
DOI: 10.1063/1.1573334
|View full text |Cite
|
Sign up to set email alerts
|

Green-light-emitting ZnSe nanowires fabricated via vapor phase growth

Abstract: Stoichiometric ZnSe nanowires have been synthesized through a vapor phase reaction of zinc and selenium powder on the (100) silicon substrate coated with a gold film of 2 nm in thickness. The microstructures and the chemical compositions of the as-grown nanowires have been investigated by means of electron microscopy, the energy dispersive spectroscopy, and Raman spectroscopy. The results reveal that the as-grown materials consist of ZnSe nanowires with diameters ranging from 5 to 50 nm. Photoluminescence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(81 citation statements)
references
References 20 publications
6
75
0
Order By: Relevance
“…We also consider that: (a) Transition metals such as Au typically behave as deep acceptors in Ⅱ-Ⅳ semiconductors [72]. Evidence of excitons bound at Au, Ag, or Cu acceptor sites was reported for bulk ZnTe [89], ZnSe [72], and also for ZnSe NWs [15]. In all cases, however, these were accompanied by the corresponding low-energy transition involving the deep acceptor site [16,72,89].…”
Section: Photoluminescence Of Individual Nanowiresmentioning
confidence: 99%
See 1 more Smart Citation
“…We also consider that: (a) Transition metals such as Au typically behave as deep acceptors in Ⅱ-Ⅳ semiconductors [72]. Evidence of excitons bound at Au, Ag, or Cu acceptor sites was reported for bulk ZnTe [89], ZnSe [72], and also for ZnSe NWs [15]. In all cases, however, these were accompanied by the corresponding low-energy transition involving the deep acceptor site [16,72,89].…”
Section: Photoluminescence Of Individual Nanowiresmentioning
confidence: 99%
“…For direct band-gap NWs, PL is often measured over large ensembles [15][16][17][18][19][20][21][22]. This, however, can hinder the extrapolation of representative features as structural inhomogeneities may be present.…”
Section: Introductionmentioning
confidence: 99%
“…These added impurities significantly affect the optical and electronic properties of the grown nanostructures. Xiang et al (2003) reported that the inclusion of Au catalyst into ZnSe nanowire results in strong green emission from the nanowire. Philipose et al (2008) reported that the ZnSe nanostructures grown in low vacuum condition exhibits stronger DL emissions than the much needed NBE emission for optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of manuscripts have been published reporting the optical properties of NWs and the emerging picture is that individual growth methods and conditions severely affect NW optical properties in terms of emission intensity, spectral width and peak, and the presence of long wavelength components from impurity states that emit radiatively. A variety of NWs made from materials including ZnO [40], ZnS [41], GaN [42], CdS [28,46], CdSe [43], ZnSe [44], InP [45], and GaAs [46], have been extensively studied by steady state and transient PL spectroscopy. High quality NWs synthesized under controlled conditions at high temperatures typically emit brightly with a spectral peak near the band-edge.…”
mentioning
confidence: 99%
“…Optical properties of nanowires Photoluminescence (PL) data collected from individual direct-bandgap NWs can reveal a wealth of information, both in terms of characterization of the material and optical properties such as band-edge emission, trap states, radiative efficiency, carrier and photon confinement [24,28,[39][40][41][42][43][44][45][46][47][48][49]. A large number of manuscripts have been published reporting the optical properties of NWs and the emerging picture is that individual growth methods and conditions severely affect NW optical properties in terms of emission intensity, spectral width and peak, and the presence of long wavelength components from impurity states that emit radiatively.…”
mentioning
confidence: 99%